Kosovo’s Experience for Children with Feeding Difficulties after Cardiac Surgery for Congenital Heart Defect - Bejiqi, Ramush (Open Access Maced J Med Sci, 2017)
BACKGROUND: A feeding disorder in infancy and during childhood is a complex condition involving different symptoms such as food refusal and faddiest, both leading to a decreased food intake. AIM: We aimed to assess the prevalence and predictor factors of feeding difficulties in children who underwent cardiac open heart surgery in neonatal period and infancy. We address selected nutritional and caloric requirements for children after cardiac surgery and explore nutritional interdependence with other system functions. METHODS: This was a retrospective study in a tertiary referral hospital, and prior approval from the institutional ethics committee was obtained. Information for 78 children (42 male and 36 female) was taken from patients charts. Data were analysed with descriptive statistics and logistic regression. RESULTS: From a cohort of analysed children with feeding problems we have occurred in 23% of such cases. At the time of the study, refusal to eat or poor appetite was reported as a significant problem in 19 children and subnormal height and weight were recorded in 11 children. Early neonatal intervention and reoperation were identified as risk factors for latter feeding difficulties or inadequate intake. Children with feeding problems also tended to eat less than children without feeding problems. There was a trend towards more feeding problems in patients with chromosomal abnormalities or other associated anomalies. CONCLUSION: Feeding disorder is often and a frequent long-term sequel in children after neonatal or early infancy heart surgery. Patients with chromosomal and associated anomalies who underwent multiple cardiac surgeries are at risk of developing feeding difficulties.